Muscle Fatigue in Shoulder Joint External Rotation due to Consecutive Pitching - YAMANAKA, Yuki; YOSHIHARA, Keisuke; URABE, Yukio (Rigakuryoho Kagaku, 2012)
[Purpose] The purpose of this study was to clarify whether the shoulder joint external rotation muscles are affected by muscle fatigue from consecutive baseball pitching. [Subject] Ten adult men who had spent more than five years playing baseball participated in this study. [Methods] The muscle activity in pitching before and after throwing 100 pitches were recorded using surface electromyography. From the recorded electromyography data, we calculated the time required to reach 50%, and 100% maximal voluntary contraction, and maximal value. We compared these values before and after throwing 100 pitches. [Results] After throwing 100 pitches, in terms of maximal value, only the electromyography data of the teres minor was delayed. The others muscles did not show any change. [Conclusion] Fatigue from consecutive baseball pitching weakened all muscles, but electromyography data were non-uniform.